(untitled) (Journal of Universal College of Medical Sciences, 2026)
INTRODUCTION The accurate laboratory reports are an essential part of the health care delivery system. The quality of a diagnostic laboratory is reflected by its accurate diagnostic results. A preanalytical error means any error in the laboratory that occurs during sample collection and transportation. This can lead to inaccurate laboratory results which can further lead to inappropriate clinical decision and can cause serious health risk to the patients. MATERIAL AND METHODS The study was conducted in Department of Pathology, Birat Medical College Teaching Hospital for 6 months (from 1 August 2022 to 31 January 2023). All the samples received in the pathology department were verified by the laboratory staff on duty for patient’s identification like name, surname, age, sex, date of sample collection, hospital registration number, bill number and relevant clinical history RESULTS Out of twenty four thousand five hundred and sixty three (24563) total samples received in pathology department, preanalytical errors were seen in one hundred and ninety four (194) samples which comprises of 0.7 percentages of total sample. Most common preanalytical errors were clotted samples which comprises of (47.42%) of all the errors. CONCLUSION Preanalytical errors can cause unnecessary panic in patients and wastage of both time and money. We can minimize preanalytical errors by regular training of laboratory staff and by virtual coordination and conversation between the sample collecting laboratory staffs.